Government Transfers and Time Allocation Decisions: The Case of Child Labour in Ethiopia. (20th August 2020) - Prifti, Ervin; Daidone, Silvio; Campora, Greta; Pace, Noemi
Abstract: We exploit the social cash transfer programme in Ethiopia to study how an increase in unearned income through a government transfer affects children's work time allocation and their school attendance rate. In rural areas, the transfer led to a half an hour reduction in the total number of hours worked, while in urban areas, transfers had the opposite impacts, worsening the child labour situation with no impacts on the share of children attending school. An insufficient transfer amount and lack of messaging on its recommended use may partly explain the mixed results on child labour and the lack of impacts on school attendance. © 2020 John Wiley & Sons, Ltd.